An investigation into stylistic devices describing nature in “the old man and the sea” by ernest hemingway and “người lái đò sông đà” by nguyễn tuân - Ngô Thị Kiều Trang (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This thesis mainly focuses on identifying and analyzing stylistic devices describing nature used in “The Old Man and the Sea” by Ernest Hemingway and “Người lái đò sông Đà” by Nguyễn Tuân. The analysis, discussion and comments have been made to point out the similarities and differences of common stylistic devices describing nature used in two works. The data of the study collected from two works were quoted, described and analyzed on the stylistic aspects under qualitative and quantitative approaches. Through the whole research, the data were classified and investigated following three categories: phonetic stylistic devices, lexical stylistic devices and syntactical stylistic devices. The paper showed that common stylistic devices describing nature used in “The Old Man and the Sea” by Ernest Hemingway and “Người lái đò sông Đà” by Nguyễn Tuân were onomatopoeia, reduplicative, simile, metaphor, personification, enumeration, inversion, climax, comparative structures and mononuclear sentence. Among these three categories, lexical stylistic devices were the most predominant ones, accounting for over 50% in both works. It can be seen that simile and personification were used the most commonly among stylistic devices investigated. Besides, phonetic stylistic devices and syntactical stylistic devices were also used to depict nature as well as emphasize writer’s implications. However, their occurrences were not always the same in two works. Finally, on the basis of contrastive analysis, some suggestions have been offered in the hope that they can partly contribute to language teaching and learning of texts describing nature